Movement disorders among adult neurological outpatients evaluated over 20 years in Guayaquil, Ecuador - Oscar H. Del Brutto; Victor J. Del Brutto (MDPI AG, 2013)
There is little information available on the evolutive pattern of patients with movement disorders in developing countries. We analyzed 579 consecutive adults with movement disorders and prospectively evaluated them at our institution (Department of Neurological Sciences, Kennedy Clinic, Guayaquil, Ecuador) from 1990 to 2009. Mean age was 62.9±17.5 years, and 50.8% were men. Patients presented with tremor/rigidity (55%), involuntary movements (23.5%) and abnormalities of stance and gait (21.5%). Overall, 45% of our patients had degenerative disorders of the nervous system. We found significant increases in the relative prevalence of tremor/rigidity and abnormalities of stance and gait, and this reflected an increase in the number of patients with degenerative diseases over the study years. We found a dynamic pattern of movement disorders over the years. Today, causes and relative prevalence of these conditions in our population is more similar to that reported from the developed world than it was 20 years ago.